2021
DOI: 10.1007/s40820-021-00763-8
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Passivation Mechanism of Imidazolium-Based Ionic Liquids on Inorganic Perovskite to Achieve Near-Record-Efficiency CsPbI2Br Solar Cells

Abstract: The application of ionic liquids in perovskite has attracted wide-spread attention for its astounding performance improvement of perovskite solar cells (PSCs). However, the detailed mechanisms behind the improvement remain mysterious. Herein, a series of imidazolium-based ionic liquids (IILs) with different cations and anions is systematically investigated to elucidate the passivation mechanism of IILs on inorganic perovskites. It is found that IILs display the following advantages: (1) They form ionic bonds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 59 publications
3
68
0
Order By: Relevance
“…It can be modified with various functional groups to passivate the surface and boundary defects. [39][40][41] For example, by adding 1-hexyl-3-methylimidazolium iodide into the FAPbI 3 DOI: 10.1002/solr.202200364 FAPbI 3 is considered one of the most ideal perovskite materials to construct highly efficient perovskite solar cell (PSC), but the poor phase stability and filmforming properties hinder further performance improvements. Herein, an ionic liquid 3-(2-amino-2-oxoethyl)-1-methyl-1H-imidazol-3-ium chloride (AOMCl) with multifunctional cations and Cl anion to assist crystallization, reduce defects, and stabilize α-FAPbI 3 is reported.…”
Section: Introductionmentioning
confidence: 99%
“…It can be modified with various functional groups to passivate the surface and boundary defects. [39][40][41] For example, by adding 1-hexyl-3-methylimidazolium iodide into the FAPbI 3 DOI: 10.1002/solr.202200364 FAPbI 3 is considered one of the most ideal perovskite materials to construct highly efficient perovskite solar cell (PSC), but the poor phase stability and filmforming properties hinder further performance improvements. Herein, an ionic liquid 3-(2-amino-2-oxoethyl)-1-methyl-1H-imidazol-3-ium chloride (AOMCl) with multifunctional cations and Cl anion to assist crystallization, reduce defects, and stabilize α-FAPbI 3 is reported.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2021) reported the use of imidazolium‐based IL containing BF 4 (1‐butyl‐2,3‐dimethylimidazolium tetrafluoroborate) that was applied as a surface passivation agent on top of CsPbI 2 Br perovskites. [ 27 ] The authors suggested that BF 4 − of the IL played an important role in the passivation of under‐coordinated Cs + /Pb 2+ by forming strong ionic interactions (Pb−F, Cs−F). The calculation result corroborated the effectiveness of superhalogen in passivation by showing its higher relative binding affinity than halide to I − vacancy, and also higher binding energy to Pb‐I antisite as shown in Figure 3c,d, respectively.…”
Section: Utilization Of Superhalogen For Perovskite Surface Treatmentmentioning
confidence: 99%
“…Although the authors did not deal with the detail of the underlying reasons for the suppression of ion migration, we conjecture that the presence of BF 4 − at the grain boundary might contribute to the suppression of the ion migration because of the high binding affinity of BF 4 − to iodide vacancy (V I + ). [ 27 ] The same research group (2020) reported the use of a different ionic compound, 1‐butyl‐1‐methylpiperidinium tetrafluoroborate ([BMP] + [BF 4 ] − ) to stabilize perovskites (Cs 0.17 FA 0.83 Pb(I 1− x Br x ) 3 ). [ 28 ] The authors addressed the detrimentality of the formation of iodine (I 2 ) under illumination on the device stability, [ 29 ] and explained that it forms due to the formation of Frenkel defects consisting of iodide vacancies and/or their interstitial pairs.…”
Section: Incorporation Of Superhalogen In the Bulk Of Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations